The uninvited - Macardle, Dorothy 1889-1958; Young, Victor 1900-1956 (Criterion collection, 2013)
A pair of siblings from London purchases a surprisingly affordable, lonely cliff-top house in Cornwall, only to discover that it actually carries a ghostly price. Soon they're caught up in a bizarre romantic triangle from beyond the grave. A tragic family past, a mysteriously locked room, cold chills, bumps in the night-this gothic Hollywood classic has it all
Based on the novel by Dorothy Macardle. - "Universal"--Opening frame. -
1.37:1 aspect ratio ; New 2K digital film restoration
Orig.: USA 1944
Special features: Giving up the ghost (new visual essay by filmmaker Michael Almereyda); Radio adaptations (DVD-Rom feature): Screen Guild Theater: August 28, 1944; Screen Director's Playhouse: November 18, 1949; Trailer. Plus, A booklet featuring an essay by critic Farran Smith Nehme and a 1997 interview with director Lewis Allen
Keywords: Macardle, Dorothy / 1889-1958 / Film adaptations; Macardle, Dorothy -- 1889-1958; Brothers and sisters / Drama; Family secrets / Drama; Haunted houses / Drama; Vacation homes / Drama; Ghosts -- United States -- Drama.; Nightmares -- United States -- Drama.; Fathers and daughters -- United States -- Drama.; Psychiatric hospital patients -- United States -- Drama.; Sisters -- United States -- Drama.; Feature films.; Thrillers (Motion pictures); Psychiatrie; Geheimnis; Familie; Albtraum; Horrorfilm; Spuk; Thriller; Patient; USA; Film; DVD-Video